1988
DOI: 10.4319/lo.1988.33.4.0624
|View full text |Cite
|
Sign up to set email alerts
|

Particulate thiols in coastal waters: The effect of light and nutrients on their planktonic production

Abstract: Reduced sulfur compounds of low molecular weight, mainly particulate glutathione, were present in concentrations up to 600 pM in Saanich Inlet and off southern California. The vertical distributions of particulate glutathione (PGSH) in Saanich Inlet showed a subsurface maximum and decreased with depth in close correspondence with chlorophyll profiles. As with other measures of phytoplankton standing stock, PGSH decreased offshore in the Southern California Bight. In response to exposure to lower than ambient l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
(16 reference statements)
0
31
1
Order By: Relevance
“…Matrai and Vetter (1988) observed that particulate GSH in Saanich Inlet, British Columbia, Canada, showed a subsurface maximum and decreased with depth in close correlation to chlorophyll profiles. In the western North Sea and English Channel, the GSH distribution in surface water from different sites was also found to co-vary with chlorophyll concentrations (AlFarawati and Van Den Berg 2001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Matrai and Vetter (1988) observed that particulate GSH in Saanich Inlet, British Columbia, Canada, showed a subsurface maximum and decreased with depth in close correlation to chlorophyll profiles. In the western North Sea and English Channel, the GSH distribution in surface water from different sites was also found to co-vary with chlorophyll concentrations (AlFarawati and Van Den Berg 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Another possible source of GSH in the oxic water is bacteria. Bacteria contain GSH and have been postulated to contribute to the observed GSH distributions in Saanich Inlet (Matrai and Vetter 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial pathways for the formation of cysteine, glutathione, and 3-MPA have been well documented in laboratory cultures and in marine sediments (Bird and Moir 1972;Salsbury and Merricks 1975;Kiene and Taylor 1988). Thiols in surface coastal wa- ters have also been attributed to marine phytoplankton (AlFarawati and Van Den Berg 2001;Matrai and Vetter 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Nanomolar to millimolar levels of thiols have been commonly reported in seawater (Matrai and Vetter 1988;Tang et al 2000a;Al-Farawati and van den Berg 2001) and marine sediment interstitial waters (Luther et al 1986; Kiene and Taylor 1988;MacCrehan and Shea 1995). They can be formed via a variety of pathways, including (1) microbial deamination of sulfur-containing amino acids (Bird and Moir 1972;Salsbury and Merricks 1975;Mopper and Taylor 1986), (2) microbial degradation of dimethylsulfoniopropionate (DMSP) (Shea and MacCrehan 1988) produced by marine algae and halophytic plants (Yoch 2002), and (3) abiotic Michael addition reaction between sulfide or polysulfides and unsaturated organic compounds (Mopper and Taylor 1986;Mopper 1987, 1989).…”
mentioning
confidence: 99%
“…Among the numerous organic sulfur compounds, organic sulfhydryls (R-SH) are especially important in biogeochemical cycling of metals in marine and freshwater ecosystems because of the high reactivity of the sulfhydryl group toward metals . Thiols have been shown to play an important role in controlling the bioavailability of trace metals and metalloids (Boulegue et al 1982;Matrai 1988;Lee and Hultberg 1990;Leal et al 1999;Harris et al 2003) in aquatic environments through complexation reactions (Cullen et al 1984;Hu et al 2006). …”
Section: Introductionmentioning
confidence: 99%